Prospective evaluation of host biomarkers other than interferon gamma in QuantiFERON Plus supernatants as candidates for the diagnosis of tuberculosis in symptomatic individuals. Issue 3 (September 2019) - Manngo, Portia M.; Gutschmidt, Andrea; Snyders, Candice I.; Mutavhatsindi, Hygon; Manyelo, Charles M.; Makhoba, Nonjabulo S.; Ahlers, Petri; Hiemstra, Andriette; Stanley, Kim; McAnda, Shirley; Kidd, Martin; Malherbe, Stephanus T.; et al.
Highlights: New tools are urgently needed for the diagnosis of TB. Biomarkers detected in QuantiFERON Plus supernatants may be useful. Unstimulated host biomarkers were more promising in this study. A six-marker unistimulated biosignature showed promise in this study. Performance of biosignatures may be influenced by HIV infection. Summary: Background: There is an urgent need for new tools for the diagnosis of TB. We evaluated the usefulness recently described host biomarkers in supernatants from the newest generation of the QuantiFERON test (QuantiFERON Plus) as tools for the diagnosis of active TB. Methods: We recruited individuals presenting at primary health care clinics in Cape Town, South Africa with symptoms requiring investigation for TB disease, prior to the establishment of a clinical diagnosis. Participants were later classified as TB or other respiratory diseases (ORD) based on the results of clinical and laboratory tests. Using a multiplex platform, we evaluated the concentrations of 37 host biomarkers in QuantiFERON Plus supernatants from study participants as tools for the diagnosis of TB. Results: Out of 120 study participants, 35(29.2%) were diagnosed with active TB, 69(57.5%) with ORD whereas 16(13.3%) were excluded. 14(11.6%) of the study participants were HIV infected. Although individual host markers showed potential as diagnostic candidates, the main finding of the study was the identification of a six-marker biosignature in unstimulated supernatants (Apo-ACIII, CXCL1, CXCL9, CCL8, CCL-1, CD56) which diagnosed TB with sensitivity and specificity of 73.9%(95% CI; 51.6–87.8) and 87.6%(95% CI; 77.2–94.5), respectively, after leave-one-out cross validation. Combinations between TB-antigen specific biomarkers also showed potential (sensitivity of 77.3% and specificity of 69.2%, respectively), with multiple biomarkers being significantly different between TB patients, Quantiferon Plus Positive and Quantiferon Plus negative individuals with ORD, regardless of HIV status. Conclusions: Biomarkers detected in QuantiFERON Plus supernatants may contribute to adjunctive diagnosis of TB.